Value of Angiography in the Diagnosis of Bony Tumors - Mendoza, Daniel D. (1963)
The diagnosis of bone tumors involves great responsibility, since an error in it would result in an error in treatment, is causing unnecessary mutilating intervention is timely losing precious time that can not be restored. The logic within research through angiography has gained great progress in recent years, is to contribute greatly in the diagnosis of bone lesions type your moral.